2022
DOI: 10.3390/polym14204465
|View full text |Cite
|
Sign up to set email alerts
|

Fire Resistance Evaluation of New Wooden Composites Containing Waste Rubber from Automobiles

Abstract: Particleboards containing waste rubber (tires and mixtures of isolators and carpets) filler were evaluated from the point of view of its flammability. The assessment of the utilization of these composites in the construction industry was analyzed through the determination of their spontaneous ignition temperatures, mass burning rate and calorific value. Based on the results of spontaneous ignition temperatures, similar values between particleboards and particleboards containing 10%, 15% and 20% of waste tires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…It is well known from the literature [23] that the addition of coal fly ash (by-product of coal burning in thermal power stations captured in electrofilters) to Portland cement concrete increases its performance, including its workability, mechanical strength, and durability, providing low proportion of interconnected pores in the concrete macrostructure and decreasing the permeability. However, in the current experiment, the proportion of fly ash was limited below 11 wt.% in order to obtain small and uniform pore sizes for the cellular concrete with moderate expansion by foaming the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known from the literature [23] that the addition of coal fly ash (by-product of coal burning in thermal power stations captured in electrofilters) to Portland cement concrete increases its performance, including its workability, mechanical strength, and durability, providing low proportion of interconnected pores in the concrete macrostructure and decreasing the permeability. However, in the current experiment, the proportion of fly ash was limited below 11 wt.% in order to obtain small and uniform pore sizes for the cellular concrete with moderate expansion by foaming the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Research by Mancel et al (2022) on the use of rubber waste (tires and insulators) as llers in the production of particleboards showed that the ignition times of boards with additives of 10%, 15% and 20% of rubber were similar to those of particleboards alone. The average time to ignition was from 298 s to 309 s. Similarly, the weight loss for the board containing 10% rubber waste additives was similar to that of the particleboard.…”
Section: Flammability Of Biocomposite Boardsmentioning
confidence: 99%
“…The use of rubber waste as fillers improved the mechanical and physical properties of the composites. In this way, composites with waste rubber fillers have created a new sustainable material and have the potential to be used in various fields [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%